Adaptation of a Composite Scale for Assessing Health-Promoting Behaviors in Adolescents and Young Adults - Soh, Gustave; Wamba, André; Chen, Mei-Yen (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2024)
Introduction. Health promoting behaviour tools abound in English, while they are scarce or almost non-existent in French. This article aimed to validate a composite questionnaire to identify health promoting or risky behaviours. Method. The ten steps of adapting psychological tests/scales provide by Gana et al. (2021) were applied to data collected from 343 adolescents and young adults aged 15-25 (mean = 17.6 ± 1.76) who completed a questionnaire of 51 items derive from three pre-existing scales. Results. Exploratory and confirmatory analyses support the eight dimensions structure with 27 items explaining 56.69% of variances: spiritual health; interpersonal relationship; physical exercise; stress management; appreciation of life; sleep hygiene; responsibility in health; and social support. Conclusion. The Composite Health Promotion Behaviour Assessment Questionnaire (AHPB-27) is valid for identifying health promoting behaviours among adolescents and young adults in the francophonie